PENGARUH INFRASTRUKTUR JALAN TOL TERHADAP PENGGUNAAN LAHAN TERBANGUN DAN KONDISI SOSIAL EKONOMI DI KAWASAN METROPOLITAN PATUNGRAYA AGUNG - Siti Yuszahra Adila; Zenia F. Saraswati (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
The development of the metropolitan area is in line with the development of toll road infrastructure. This has implications for changes in the use of built-up land, population and economy. The areas most affected by the construction are located around the entrances and exits of the toll gates. However, along with changes in the use of built-up land that continues to grow, the amount of land available is limited. So that it can cause a mismatch of land use designation with the designation plan. Based on these problems, it is necessary to study the effect of toll road infrastructure development on changes in built-up land use, population and economy. The results showed that there was an increase in built-up land covering an area of ​​3,148.31 Ha, population of 273,997 people and in several PDRB sectors. Meanwhile, based on the results of changes in built-up land against the suitability of the South Sumatra Province Spatial Planning there are only 75.69% of the area of ​​built-up land that is in accordance with its designation. It is necessary to evaluate changes in built up land in Patungraya Agung Metropolitan Area so that land changes are built in accordance with efficient spatial planning.